Iodine and Myo-Inositol: A Novel Promising Combination for Iodine Deficiency - Barbaro, Daniele; Orrù, Beatrice; Unfer, Vittorio (Frontiers in Endocrinology, 2019)
Despite universal salt iodization programmes implemented over the last decades, iodine deficiency remains a major public health problem in many countries worldwide. Endeavors are still required to ensure sufficient iodine intake in the populations at risk in order to eliminate deficiency. Iodine is crucial for the synthesis of thyroid hormones triiodothyronine (T3) and thyroxine (T4), as well as for the thyroid health. When iodine levels are insufficient, T4 attests towards the lower limit of the physiological range, causing subtle fluctuations in the T3:T4 ratio. Monitoring these variations may be an accurate way to assess patient’s iodine status. Recently, a number of published clinical studies documented a growing interest toward the use of myo-inositol in thyroid diseases. Myo-inositol, a carbocyclic polyol, regulates the generation of hydrogen peroxide (H2O2) in thyrocytes, crucial for iodine organification and thyroid hormone biosynthesis. Thus, combined supplementation of iodine and myo-inositol may promote higher iodine availability in thyrocytes improving thyroid functionality. This review presents novel strategies for the diagnosis and the management of iodine deficiency, focusing on the potential role of myo-inositol combined with iodine.